Intergenerational Transmission of Corporal Punishment: The Independent and Interactive Moderating Role of Children’s Negative Affectivity and Effortful Control - Wang, Meifang (Journal of interpersonal violence, 2021)
The present study examined the independent and interactive moderating effects of children’s negative affectivity (NA) and effortful control (EC) on the relations between parental childhood history of corporal punishment (CP) and their current use of CP. A total of 634 Chinese father–mother dyads with preschoolers (M age = 4.69 years, 53.8% boys) reported on their experience of CP in childhood, their current use of CP toward children, and their children’s NA and EC. For both mothers and fathers, hierarchical regression analyses revealed that children’s NA and EC independently and interactively moderated the relations between parental childhood history of CP and their current use of CP. Specifically, high NA intensified but high EC weakened the relations between parental childhood history of CP and their current use of CP. Moreover, high EC also weakened the intensifying effect of NA, with the intergenerational stability of CP being weakest and even disrupted when children were at low NA and high EC meanwhile. Findings from the present study highlight the importance of considering how the child factor may influence the intergenerational transmission of CP.